Evaluation of the clinicoradiological profile in cases of allergic bronchopulmonary aspergillosis: An original research - Ganipineni Vijay Durga Pradeep; Rajunaik Ajmeera; Rohit K Jha; Mallareddy Medikonda; Rehan Saifuddin; Faziljot Singh (Wolters Kluwer Medknow Publications, 2023)
Introduction: A complicated hypersensitive reaction to inhaled fungal antigens results in allergic bronchopulmonary aspergillosis (ABPA), an immunologic pulmonary disease. ABPA complicates nearly 2% of instances of persistent asthma as well as nearly 10% of chronic cases of steroid-dependent asthma, and it occurs most frequently in immunocompetent patients. The purpose of the current research was to analyze the radiological and clinical features of the participants as well as the serological association of ABPA. Materials and Methods: From April 2020 to April 2021, a retrospective investigation was conducted. The study included patients based on the International Society for Human and Animal Mycology's criteria for ABPA confirmation. Analysis was done on the demographic information and pathological and radiological test results of the patients. The patients' pre-bronchodilator and post-bronchodilator spirometry was compared, and asthmatic control was estimated. Results: A total of 50 patients were investigated at in this study. Demographic findings indicated young subjects and aa female predominance. Cough was the most prevalent symptom in 84% of patients. Asthma of the bronchi was a risk factor for all of the patients. The mean serum immunoglobulin E level and the mean absolute eosinophil count were 533 cells/L and 2269 UI/mL, respectively. Spirometry results from the study's participants indicated an obstructive pattern in about 80% of cases. The most typical radiological abnormality observed was bronchiectasis, followed by parenchymal opacities. Conclusion: In conclusion, when treating asthma that is challenging to control, the diagnosis of ABPA must be taken into account. Delay in diagnosis might result in declining lung function, worsening asthma control, possibly irreversible alterations, greater treatment costs, and declined quality of life.